The Porous Formation in Contemporary Architecture - Abbood, Attaa Hasan (Iraqi Journal of Architecture and Planning, 2018)
The porosity is one of the concepts which is adopted in contemporary architecture to enhance the production of innovative and unique architectural configurations and forms. It is characterized by balance and integration to achieve the best environmental, aesthetic and functional standards in the architectural building, in line with the technical and technological progress. The research problem was articulated as: the lack of comprehensive framework, of porous formation in terms of its nature, characteristics and rules of formation in contemporary architecture. The aim of research is to introduce this knowledge by adopting the descriptive and analytical approach to a number of architectural studies in order to identify the main vocabulary that define the porous formation and its application to a number of selected projects that distinguish it by investing in the porous formation. The research assumed the adoption of different formations with multiple and varied patterns according to various rules and mechanisms of formation. The research reached to a set of theoretical and practical conclusions concerning the methods and rules of the adoption of the